{-# LANGUAGE CPP, RankNTypes #-}
{-| A monad morphism is a natural transformation:
> morph :: forall a . m a -> n a
... that obeys the following two laws:
> morph $ do x <- m = do x <- morph m
> f x morph (f x)
>
> morph (return x) = return x
... which are equivalent to the following two functor laws:
> morph . (f >=> g) = morph . f >=> morph . g
>
> morph . return = return
Examples of monad morphisms include:
* 'lift' (from 'MonadTrans')
* 'squash' (See below)
* @'hoist' f@ (See below), if @f@ is a monad morphism
* @(f . g)@, if @f@ and @g@ are both monad morphisms
* 'id'
Monad morphisms commonly arise when manipulating existing monad transformer
code for compatibility purposes. The 'MFunctor', 'MonadTrans', and
'MMonad' classes define standard ways to change monad transformer stacks:
* 'lift' introduces a new monad transformer layer of any type.
* 'squash' flattens two identical monad transformer layers into a single
layer of the same type.
* 'hoist' maps monad morphisms to modify deeper layers of the monad
transformer stack.
-}
module Control.Monad.Morph (
-- * Functors over Monads
MFunctor(..),
generalize,
-- * Monads over Monads
MMonad(..),
MonadTrans(lift),
squash,
(>|>),
(<|<),
(=<|),
(|>=)
-- * Tutorial
-- $tutorial
-- ** Generalizing base monads
-- $generalize
-- ** Monad morphisms
-- $mmorph
-- ** Mixing diverse transformers
-- $interleave
-- ** Embedding transformers
-- $embed
) where
import Control.Monad.Trans.Class (MonadTrans(lift))
import qualified Control.Monad.Trans.Error as E
#if MIN_VERSION_transformers(0,4,0)
import qualified Control.Monad.Trans.Except as Ex
#endif
import qualified Control.Monad.Trans.Identity as I
import qualified Control.Monad.Trans.List as L
import qualified Control.Monad.Trans.Maybe as M
import qualified Control.Monad.Trans.Reader as R
import qualified Control.Monad.Trans.RWS.Lazy as RWS
import qualified Control.Monad.Trans.RWS.Strict as RWS'
import qualified Control.Monad.Trans.State.Lazy as S
import qualified Control.Monad.Trans.State.Strict as S'
import qualified Control.Monad.Trans.Writer.Lazy as W'
import qualified Control.Monad.Trans.Writer.Strict as W
import Data.Monoid (Monoid, mappend)
import Data.Functor.Compose (Compose (Compose))
import Data.Functor.Identity (runIdentity)
import Data.Functor.Product (Product (Pair))
#if MIN_VERSION_transformers(0,3,0)
import Control.Applicative.Backwards (Backwards (Backwards))
import Control.Applicative.Lift (Lift (Pure, Other))
#endif
-- For documentation
import Control.Exception (try, IOException)
import Control.Monad ((=<<), (>=>), (<=<), join)
import Data.Functor.Identity (Identity)
{-| A functor in the category of monads, using 'hoist' as the analog of 'fmap':
> hoist (f . g) = hoist f . hoist g
>
> hoist id = id
-}
class MFunctor t where
{-| Lift a monad morphism from @m@ to @n@ into a monad morphism from
@(t m)@ to @(t n)@
-}
hoist :: (Monad m) => (forall a . m a -> n a) -> t m b -> t n b
instance MFunctor (E.ErrorT e) where
hoist nat m = E.ErrorT (nat (E.runErrorT m))
#if MIN_VERSION_transformers(0,4,0)
instance MFunctor (Ex.ExceptT e) where
hoist nat m = Ex.ExceptT (nat (Ex.runExceptT m))
#endif
instance MFunctor I.IdentityT where
hoist nat m = I.IdentityT (nat (I.runIdentityT m))
instance MFunctor L.ListT where
hoist nat m = L.ListT (nat (L.runListT m))
instance MFunctor M.MaybeT where
hoist nat m = M.MaybeT (nat (M.runMaybeT m))
instance MFunctor (R.ReaderT r) where
hoist nat m = R.ReaderT (\i -> nat (R.runReaderT m i))
instance MFunctor (RWS.RWST r w s) where
hoist nat m = RWS.RWST (\r s -> nat (RWS.runRWST m r s))
instance MFunctor (RWS'.RWST r w s) where
hoist nat m = RWS'.RWST (\r s -> nat (RWS'.runRWST m r s))
instance MFunctor (S.StateT s) where
hoist nat m = S.StateT (\s -> nat (S.runStateT m s))
instance MFunctor (S'.StateT s) where
hoist nat m = S'.StateT (\s -> nat (S'.runStateT m s))
instance MFunctor (W.WriterT w) where
hoist nat m = W.WriterT (nat (W.runWriterT m))
instance MFunctor (W'.WriterT w) where
hoist nat m = W'.WriterT (nat (W'.runWriterT m))
instance Functor f => MFunctor (Compose f) where
hoist nat (Compose f) = Compose (fmap nat f)
instance MFunctor (Product f) where
hoist nat (Pair f g) = Pair f (nat g)
#if MIN_VERSION_transformers(0,3,0)
instance MFunctor Backwards where
hoist nat (Backwards f) = Backwards (nat f)
instance MFunctor Lift where
hoist _ (Pure a) = Pure a
hoist nat (Other f) = Other (nat f)
#endif
-- | A function that @generalize@s the 'Identity' base monad to be any monad.
generalize :: Monad m => Identity a -> m a
generalize = return . runIdentity
{-# INLINABLE generalize #-}
{-| A monad in the category of monads, using 'lift' from 'MonadTrans' as the
analog of 'return' and 'embed' as the analog of ('=<<'):
> embed lift = id
>
> embed f (lift m) = f m
>
> embed g (embed f t) = embed (\m -> embed g (f m)) t
-}
class (MFunctor t, MonadTrans t) => MMonad t where
{-| Embed a newly created 'MMonad' layer within an existing layer
'embed' is analogous to ('=<<')
-}
embed :: (Monad n) => (forall a . m a -> t n a) -> t m b -> t n b
{-| Squash two 'MMonad' layers into a single layer
'squash' is analogous to 'join'
-}
squash :: (Monad m, MMonad t) => t (t m) a -> t m a
squash = embed id
{-# INLINABLE squash #-}
infixr 2 >|>, =<|
infixl 2 <|<, |>=
{-| Compose two 'MMonad' layer-building functions
('>|>') is analogous to ('>=>')
-}
(>|>)
:: (Monad m3, MMonad t)
=> (forall a . m1 a -> t m2 a)
-> (forall b . m2 b -> t m3 b)
-> m1 c -> t m3 c
(f >|> g) m = embed g (f m)
{-# INLINABLE (>|>) #-}
{-| Equivalent to ('>|>') with the arguments flipped
('<|<') is analogous to ('<=<')
-}
(<|<)
:: (Monad m3, MMonad t)
=> (forall b . m2 b -> t m3 b)
-> (forall a . m1 a -> t m2 a)
-> m1 c -> t m3 c
(g <|< f) m = embed g (f m)
{-# INLINABLE (<|<) #-}
{-| An infix operator equivalent to 'embed'
('=<|') is analogous to ('=<<')
-}
(=<|) :: (Monad n, MMonad t) => (forall a . m a -> t n a) -> t m b -> t n b
(=<|) = embed
{-# INLINABLE (=<|) #-}
{-| Equivalent to ('=<|') with the arguments flipped
('|>=') is analogous to ('>>=')
-}
(|>=) :: (Monad n, MMonad t) => t m b -> (forall a . m a -> t n a) -> t n b
t |>= f = embed f t
{-# INLINABLE (|>=) #-}
instance (E.Error e) => MMonad (E.ErrorT e) where
embed f m = E.ErrorT (do
x <- E.runErrorT (f (E.runErrorT m))
return (case x of
Left e -> Left e
Right (Left e) -> Left e
Right (Right a) -> Right a ) )
#if MIN_VERSION_transformers(0,4,0)
instance MMonad (Ex.ExceptT e) where
embed f m = Ex.ExceptT (do
x <- Ex.runExceptT (f (Ex.runExceptT m))
return (case x of
Left e -> Left e
Right (Left e) -> Left e
Right (Right a) -> Right a ) )
#endif
instance MMonad I.IdentityT where
embed f m = f (I.runIdentityT m)
instance MMonad L.ListT where
embed f m = L.ListT (do
x <- L.runListT (f (L.runListT m))
return (concat x))
instance MMonad M.MaybeT where
embed f m = M.MaybeT (do
x <- M.runMaybeT (f (M.runMaybeT m))
return (case x of
Nothing -> Nothing
Just Nothing -> Nothing
Just (Just a) -> Just a ) )
instance MMonad (R.ReaderT r) where
embed f m = R.ReaderT (\i -> R.runReaderT (f (R.runReaderT m i)) i)
instance (Monoid w) => MMonad (W.WriterT w) where
embed f m = W.WriterT (do
~((a, w1), w2) <- W.runWriterT (f (W.runWriterT m))
return (a, mappend w1 w2) )
instance (Monoid w) => MMonad (W'.WriterT w) where
embed f m = W'.WriterT (do
((a, w1), w2) <- W'.runWriterT (f (W'.runWriterT m))
return (a, mappend w1 w2) )
{- $tutorial
Monad morphisms solve the common problem of fixing monadic code after the
fact without modifying the original source code or type signatures. The
following sections illustrate various examples of transparently modifying
existing functions.
-}
{- $generalize
Imagine that some library provided the following 'S.State' code:
> import Control.Monad.Trans.State
>
> tick :: State Int ()
> tick = modify (+1)
... but we would prefer to reuse @tick@ within a larger
@('S.StateT' Int 'IO')@ block in order to mix in 'IO' actions.
We could patch the original library to generalize @tick@'s type signature:
> tick :: (Monad m) => StateT Int m ()
... but we would prefer not to fork upstream code if possible. How could
we generalize @tick@'s type without modifying the original code?
We can solve this if we realize that 'S.State' is a type synonym for
'S.StateT' with an 'Identity' base monad:
> type State s = StateT s Identity
... which means that @tick@'s true type is actually:
> tick :: StateT Int Identity ()
Now all we need is a function that @generalize@s the 'Identity' base monad
to be any monad:
> import Data.Functor.Identity
>
> generalize :: (Monad m) => Identity a -> m a
> generalize m = return (runIdentity m)
... which we can 'hoist' to change @tick@'s base monad:
> hoist :: (Monad m, MFunctor t) => (forall a . m a -> n a) -> t m b -> t n b
>
> hoist generalize :: (Monad m, MFunctor t) => t Identity b -> t m b
>
> hoist generalize tick :: (Monad m) => StateT Int m ()
This lets us mix @tick@ alongside 'IO' using 'lift':
> import Control.Monad.Morph
> import Control.Monad.Trans.Class
>
> tock :: StateT Int IO ()
> tock = do
> hoist generalize tick :: (Monad m) => StateT Int m ()
> lift $ putStrLn "Tock!" :: (MonadTrans t) => t IO ()
>>> runStateT tock 0
Tock!
((), 1)
-}
{- $mmorph
Notice that @generalize@ is a monad morphism, and the following two proofs
show how @generalize@ satisfies the monad morphism laws. You can refer to
these proofs as an example for how to prove a function obeys the monad
morphism laws:
> generalize (return x)
>
> -- Definition of 'return' for the Identity monad
> = generalize (Identity x)
>
> -- Definition of 'generalize'
> = return (runIdentity (Identity x))
>
> -- runIdentity (Identity x) = x
> = return x
> generalize $ do x <- m
> f x
>
> -- Definition of (>>=) for the Identity monad
> = generalize (f (runIdentity m))
>
> -- Definition of 'generalize'
> = return (runIdentity (f (runIdentity m)))
>
> -- Monad law: Left identity
> = do x <- return (runIdentity m)
> return (runIdentity (f x))
>
> -- Definition of 'generalize' in reverse
> = do x <- generalize m
> generalize (f x)
-}
{- $interleave
You can combine 'hoist' and 'lift' to insert arbitrary layers anywhere
within a monad transformer stack. This comes in handy when interleaving two
diverse stacks.
For example, we might want to combine the following @save@ function:
> import Control.Monad.Trans.Writer
>
> -- i.e. :: StateT Int (WriterT [Int] Identity) ()
> save :: StateT Int (Writer [Int]) ()
> save = do
> n <- get
> lift $ tell [n]
... with our previous @tock@ function:
> tock :: StateT Int IO ()
However, @save@ and @tock@ differ in two ways:
* @tock@ lacks a 'W.WriterT' layer
* @save@ has an 'Identity' base monad
We can mix the two by inserting a 'W.WriterT' layer for @tock@ and
generalizing @save@'s base monad:
> import Control.Monad
>
> program :: StateT Int (WriterT [Int] IO) ()
> program = replicateM_ 4 $ do
> hoist lift tock
> :: (MonadTrans t) => StateT Int (t IO) ()
> hoist (hoist generalize) save
> :: (Monad m) => StateT Int (WriterT [Int] m ) ()
>>> execWriterT (runStateT program 0)
Tock!
Tock!
Tock!
Tock!
[1,2,3,4]
-}
{- $embed
Suppose we decided to @check@ all 'IOException's using a combination of
'try' and 'ErrorT':
> import Control.Exception
> import Control.Monad.Trans.Class
> import Control.Monad.Trans.Error
>
> check :: IO a -> ErrorT IOException IO a
> check io = ErrorT (try io)
... but then we forget to use @check@ in one spot, mistakenly using 'lift'
instead:
> program :: ErrorT IOException IO ()
> program = do
> str <- lift $ readFile "test.txt"
> check $ putStr str
>>> runErrorT program
*** Exception: test.txt: openFile: does not exist (No such file or directory)
How could we go back and fix 'program' without modifying its source code?
Well, @check@ is a monad morphism, but we can't 'hoist' it to modify the
base monad because then we get two 'E.ErrorT' layers instead of one:
> hoist check :: (MFunctor t) => t IO a -> t (ErrorT IOException IO) a
>
> hoist check program :: ErrorT IOException (ErrorT IOException IO) ()
We'd prefer to 'embed' all newly generated exceptions in the existing
'E.ErrorT' layer:
> embed check :: ErrorT IOException IO a -> ErrorT IOException IO a
>
> embed check program :: ErrorT IOException IO ()
This correctly checks the exceptions that slipped through the cracks:
>>> import Control.Monad.Morph
>>> runErrorT (embed check program)
Left test.txt: openFile: does not exist (No such file or directory)
-}